Analisis Yuridis Penyelenggaraan Uji Coba Sekolah Swasta Gratis di Provinsi Daerah Khusus Jakarta Pasca Putusan Mahkamah Konstitusi Nomor 3/Puu-Xxii/2024 - Samsudin Jagat Saputra (Indonesian Journal Publisher, 2026)
This study aims to examine in depth the constitutionality of free basic education in private schools as affirmed in Constitutional Court Decision No. 3/PUU-XXII/2024, as well as its implementation by the Government of the Special Capital Region of Jakarta Province in providing free basic education in private schools. This research employs a normative juridical legal research method, using a statutory approach and a case approach. Legal materials consist of primary, secondary, and tertiary sources, all of which are analyzed through descriptive qualitative methods. The findings indicate that Constitutional Court Decision No. 3/PUU-XXII/2024 firmly establishes free basic education as a constitutional right and a fundamental human right that must be fulfilled by the state without discrimination between public and private schools. Through a progressive constitutional interpretation, the Court positions the obligation to finance basic education as an imperative mandate of the state that must be carried out by all levels of government, both central and regional. The implementation of free basic education in private schools by the Government of the Special Capital Region of Jakarta Province represents a concrete follow-up to the Constitutional Court’s decision, which is final and legally binding. The pilot program conducted in 40 private schools may serve as a national pioneer in implementing the decision to promote equitable access to education and improve human resource development. Moreover, this policy has the potential not only to expand educational access but also to enhance the equal distribution of educational quality, provided it is supported by complementary policies such as teacher redistribution and strengthened educational governance.